Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Semangat Kerja Karyawan PT.Telkom Tenggarong - Nilam Anggar Sari (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract :The purpose of this study is to analyze the effect of work motivation and work environtment on work spirit. The research was conducted at PT.Telkom Tenggarong. The population in this research is 43 employees with sampling using census approach. The data were collected by observation, interview and questionnaire. Analyzer used is multiple linear regressions. The result of this research is, partially and simultaneously, work motivation and work environtment has positive and significant effect to work spirit. The analysis using the coefficient of determination work motivation and work environtment simultaneously variable influence on work spirit by 71,1 % while the remaining 28.9 % is the influence of other variables not examined in this study such as compensation and leadership styleMeanwhile, the variable which has dominant influence to the work spirit is work environtment because its partial coefficient determination is the biggest when it is compared to other variables. Keywords: Work Motivation, Job Satisfaction, Organizational Commitment